2021
DOI: 10.1177/20427530211039710
|View full text |Cite
|
Sign up to set email alerts
|

We are in the “breakout room.” Now what? An e-portfolio study of virtual team processes involving undergraduate online learners

Abstract: The COVID-19 pandemic, resulting in unprecedented campus closures and social distancing, has reinforced the value of learning using a virtual teamwork format. While a large body of research focuses on the inputs (members’ skills, motivation, technology, and virtuality) and outcomes (satisfaction, performance, and learning) of virtual teamwork, to date, only a limited number of studies have explored virtual teamwork processes involving university students. By drawing on the team processes model ( Marks et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 70 publications
1
19
0
1
Order By: Relevance
“…The six suggested domains are multiple dimensions of EMI pedagogy, which is supported by related studies [7,54,[103][104][105][106][107][108][109]. For example, Macaro's measures of quality interaction in pedagogy place emphasis on the meta-linguistic aspects of interaction (e.g., the use of a wide variety of teacher language functions), while the remaining four measures seem to have been designed as instructional (e.g., extended Initiation-Response-Feedback) as well as (meta)cognitive interventions (e.g., teachers posing questions that require highlevel cognitive responses from students, allowing long student turns to help them express higher-level concepts, and giving students sufficient time to allow the thinking process to occur).…”
Section: Multi-dimensionalitysupporting
confidence: 69%
See 1 more Smart Citation
“…The six suggested domains are multiple dimensions of EMI pedagogy, which is supported by related studies [7,54,[103][104][105][106][107][108][109]. For example, Macaro's measures of quality interaction in pedagogy place emphasis on the meta-linguistic aspects of interaction (e.g., the use of a wide variety of teacher language functions), while the remaining four measures seem to have been designed as instructional (e.g., extended Initiation-Response-Feedback) as well as (meta)cognitive interventions (e.g., teachers posing questions that require highlevel cognitive responses from students, allowing long student turns to help them express higher-level concepts, and giving students sufficient time to allow the thinking process to occur).…”
Section: Multi-dimensionalitysupporting
confidence: 69%
“…For example, Macaro's measures of quality interaction in pedagogy place emphasis on the meta-linguistic aspects of interaction (e.g., the use of a wide variety of teacher language functions), while the remaining four measures seem to have been designed as instructional (e.g., extended Initiation-Response-Feedback) as well as (meta)cognitive interventions (e.g., teachers posing questions that require highlevel cognitive responses from students, allowing long student turns to help them express higher-level concepts, and giving students sufficient time to allow the thinking process to occur). In addition, lecturer-student and student-student interactions in the EMI context indeed transcend linguistic and metacognitive territories [54,[103][104][105][106]110], and may be closely linked to other realms such as the socio-cultural and affective [50,108,109,[111][112][113][114]. For example, several studies explored Asian university students' perceptions of their reluctance in verbal EMI classroom participation, often claiming shyness and poor speaking skills as key determinants [55,115].…”
Section: Multi-dimensionalitymentioning
confidence: 99%
“…Therefore, the inquiry methods, especially those related to observation, problem identification, question formulation, data collection and analysis provide a framework for the construction of intra-cultural knowledge and elevate learners' self-reflection and self-awareness skills. Some recent related studies also pointed to the possibility of broader application of such learning models in both face-to-face classroom and virtual teamwork environments (Ismailov and Laurier 2021;Ismailov 2021b). Such socially interactive activities could not only enhance students' intercultural learning and communication, but most crucially improve their engagement and motivation to learn (Ismailov and Ono 2021).…”
Section: Where Next?mentioning
confidence: 99%
“…Previous studies found that courses that were blended with live and interactive approaches satisfied students’ intrinsic needs and expectations ( Cassidy, 2016 ; Ismailov and Ono, 2021 ). Additionally, by feeling closely connected with peers and teachers, learners experience better inclusion and belonging ( Ryan and Deci, 2017 ; Chiu, 2021a ; Ismailov and Laurier, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the research also points out that the affective response may vary depending on the course and its perceived utility and on whether the courses are blended with traditional approaches to meet students’ intrinsic needs and expectations ( Cassidy, 2016 ). One of the expectations in both asynchronous, synchronous, and blended courses is the need for socialization and connection with peers and teachers ( Ismailov and Laurier, 2021 ; Ismailov and Ono, 2021 ). Studies emphasize the importance of socialization and collaborative learning using various social networking tools, such as Twitter, Facebook or LMS-embedded chats ( Wang et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%